Perancangan Motion Graphic Sebagai Media Edukasi Pencegahan Hiv/Aids Bagi Kalangan Dewasa Awal - Al Habib; Joni Saputra; Syahrani Lonang (LPPM Universitas Qamarul Huda Badaruddin, 2025)
HIV/AIDS remains a health issue that requires serious attention, especially among early adults who have high social activity. Limited knowledge about transmission and prevention, along with persistent stigma in society, makes HIV/AIDS education less effective. This study aims to design motion graphic-based educational media so that HIV/AIDS prevention information becomes more engaging, easier to understand, and suitable for the characteristics of early adults. The methods used include a literature review, observation, and audience needs analysis, followed by concept development, storyboard creation, visual design, and production. The result is an educational motion graphic video that explains HIV/AIDS, modes of transmission, prevention strategies, and encourages healthy behavior and non-discriminatory attitudes toward people living with HIV/AIDS. This media is expected to improve early adults’ knowledge, awareness, and positive attitudes toward HIV/AIDS prevention.